Microbiological and Biochemical Changes of Freshwater Prawns (Macrobrachium Rosenbergii) During Storage - Abu Bakar, Fatimah (2001)
Tropical freshwater prawns are of considerable interest because of the importance of this commodity in international trade. They are one of the highest valued products in international fisheries trade and as such have good long term potential. Studies on the bacteriological and biochemical changes 'of pond water and cultured freshwater prawns were carried out to evaluate the relationship between water quality and microbiological changes during storage. Prawns were taken from three sampling sites viz: Site 1- Kg. Jumbang, Negri Sembilan; Site 2- Kg. Cangkat Tin, Perak and Site 3- Kg. Cenderiang, Perak. They were then stored at 3 different storage conditions: 1) 20 d at ambient (280 ± 2°C); 2) 10 d at 100 ± 2°C and 3) 16 d at iced storage (4° ± 2°C). Microbiological analysis was performed for total mesophilic and psychrophilic aerobic COWlts, proteolytic bacterial COWlts, histamine producing bacteria, cadaverine producing bacteria and putrescine producing bacteria in the prawns and pond water for the three sites using appropriate bacteriological agar media. Biochemical analysis was carried out for pH profiles using pH meter, freshness in terms of K-values from the test paper strips, amino acids profiles using the amino acid analyser, total volatile bases (TVB) and total volatile acids (TVA) from the distillation methods and biogenic amines viz; histamine, cadaverine and putrescine using the high performance liquid chromatography (HPLC) method. Results obtained showed that the microbiological quality of freshwater prawns was related to the micro flora of pond water where they were grown. The initial counts indicated the values were in the range of log 4+ CFU/g for all samples. Total mesophilic and psychrophilic counts of the head regions were higher than that of the body regions for all prawn samples and types of growth media tested. All samples showed an increase in counts with time and temperature of storage up to log 7+ CFU/g for mesophilic counts after 12 hat ambient, 6 d at lO˚C and 12 d at iced storage. Site 2 samples had relatively higher counts as compared to that of the other two sites which correlated well with the levels determined in their pond water. Similar trends were observed for psychrophilic counts but at lower values for different types of media studied. Biochemical results showed similar trends of increment in values and were closely related to the microbiological data until spoilage set in. Effect of preservatives on quality changes, biogenic amines production and shelf life of prawns during iced storage were investigated by sensory, microbiological, physical and chemical analyses. Sensory results indicated that the whole prawns had a shelf life of about 20 d when treated with 2% sucrose, boric acid, lactic acid, sodium chloride, and sodium metabisulfite except for control which had only 15 d shelf life. Boric acid, lactic acid and sodium metabisulfite managed to inhibit psychrophilic bacteria and biogenic amines formation in prawns while maintaining the mesophilic counts at lower levels during iced storage. Different analytical methods for the determination of histamine in prawns were evaluated. Use of enzymatic methods in the form of oxygen electrode and spectrophotometer offered excellent alternative methods for determination of histamine in freshwater prawns. The experimental results showed there was an increase of histamine measured by the oxygen electrode and very good correlation of above 0.98 with the HPLC analyser for all samples. Recovery percentages of about 100% for values of histamine between 0-200 µg/g was observed. Similarly, use of spectrophotometer with coupled diamine oxidase and horseradish peroxidase in the system allowed a semi quantitative estimation of histamine in prawns. Correlation coefficients of r2 = 0.99 were observed when compared to that of the HPLC method. Percentages of recovery of histamine in augmented samples were also about 100% for concentration of histamine between 0-200 µg/g.